The dress shop of dreams - Praag, Menna van (Allison & Busby Limited, 2015)
"For fans of Alice Hoffman, Sarah Addison Allen, and Adriana Trigiani, The Dress Shop of Dreams is a captivating novel of enduring hopes, second chances, and the life-changing magic of true love. Since her parents' mysterious deaths many years ago, scientist Cora Sparks has spent her days in the safety of her university lab or at her grandmother Etta's dress shop. Tucked away on a winding Cambridge street, Etta's charming tiny store appears quite ordinary to passersby, but the colorfully vibrant racks of beaded silks, delicate laces, and jewel-toned velvets hold bewitching secrets: With just a few stitches from Etta's needle, these gorgeous gowns have the power to free a woman's deepest desires. Etta's dearest wish is to work her magic on her granddaughter. Cora's studious, unromantic eye has overlooked Walt, the shy bookseller who has been in love with her forever. Determined not to allow Cora to miss her chance at happiness, Etta sews a tiny stitch into Walt's collar, hoping to give him the courage to confess his feelings to Cora. But magic spells--like true love--can go awry. After Walt is spurred into action, Etta realizes she's set in motion a series of astonishing events that will transform Cora's life in extraordinary and unexpected ways. Advance praise for The Dress Shop of Dreams "Bighearted, beautiful, and brushed with magic, this novel celebrates life's moments of joy, possibility, and transformation. Menna van Praag's writing is bright with sparkles and lovely grace notes."--Susan Wiggs, bestselling author of The Beekeeper's Ball Look for special features inside. Join the Random House Reader's Circle for author chats and more"--